Determinants of employee participation in physical activity: critical review of the literature - Kaewthummanukul T. (2014)
The purpose of this article is to provide a review of research literature related to factors that influence employee participation in physical activity. Eleven published studies investigating physical activity in samples of adult employees were included in this review. Across these studies, self-efficacy, or belief in personal ability to perform this health behavior, was the best predictor of physical activity among employees. Perceived benefits of physical activity and perceived health status were also found to influence participation in physical activity. Occupational health nurses could offer self-care classes and intervention programs that assist employees in improving their perceptions of self-efficacy to perform physical activity. Additionally, occupational health nurses should continue to reinforce the benefits of physical activity in all health promotion venues.